Avaliação do emprego de pirólise como etapa de processo de economia circular na valorização de resíduo de grãos defeituosos de café do processamento com fluidos pressurizados - Silva, Wenes Ramos da (2021)
The valorization of defective coffee beans (GDC) was previously proposed in the literature using pressurized fluids for oil recovery. In this work, was proposed the use of residual biomasses from extraction processes, using propane (GDC-PP) or CO2+propane (GDC-PCP), as feedstock for the pyrolysis process. The reintroduction into the production chain and valorization of these residual biomasses were evaluated through microscale pyrolysis experiments at 500 °C. In natura and residual biomasses were characterized by elemental, immediate and FTIR analysis. The biomasses with higher contents of extracted oil showed a reduction in carbon content, as well as, in general, higher moisture contents than that found in GDC in natura. By FTIR it was observed that the conditions of the extraction processes did not change the chemical functional groups of the residual biomasses. The pyrolysis experiments revealed that the biomass from the processes that had the highest contents of extracted oil (Prop 3, Prop 7, CO2+Prop 10 and CO2+Prop 12), showed a yield reduction of the total net fraction produced (bio-oil + aqueous fraction), being between 52.5 to 54.1%, and increase in biochar yields, being between 26.3 to 29.0%, and pyrolysis gas, between 18.0 to 19.5%, when compared with the in natura biomass, which presented a yield of 59.4% of total net fraction, 23.6% of biochar and 17.0% of pyrolysis gas. In general, the bio-oils showed no differences in chemical composition determined by GC/MS, only variations in the concentration of some species. The classes that showed the greatest variations in concentrations were phenolic compounds and carboxylic acids classes, with relative areas ranging from 19.7 to 43.6% and from 44.8 to 9.0%, respectively. The characterization of the liquid fractions by HRMS showed that the molecular composition was not changed despite the biomass having gone through the extraction process under different processing conditions, however, the oil contents extracted from the biomasses directly affected the yields of the pyrolysis products.